Hal Kochs "Jeg anklager Rigsdagen". En efterkrigstidsdebat i perspektiv - Ejsing, Martin Christensen (Passage - Tidsskrift for litteratur og kritik, 2011)
Martin Ejsing Christensen: “Hal Koch’s Jeg anklager Rigsdagen: A Post Second World War Debate in Perspective” In his 1947 book Jeg anklager Rigsdagen [I accuse the parliament], the Danish theologian and public commentator Hal Koch vehemently condemned the treatment of the so-called collaborators in the aftermath of the German occupation of Denmark. Today Hal Koch’s moral condemnation and its presupposed historical analysis have been lauded by several historians as the moral and historical truth about the “Retsopgør”, the transitional justice of the postwar period. This article examines this received view by placing Hal Koch’s book in its contemporary setting through an analysis of newspaper reviews of the book. Combined with the existing knowledge about the political conditions in Denmark immediately after the Second World War, this leads to the conclusion that Hal Koch’s and today’s moral condemnation of the “Retsopgør” fails to take into account some of the political circumstances obtaining at the time. As a consequence, this moral condemnation may be seen as a symptom of a more general moralizing attitude today towards the Second World War in Danish history.